Regulation of Fear Extinction in the Basolateral Amygdala by Dopamine D2 Receptors Accompanied by Altered GluR1, GluR1-Ser845 and NR2B Levels - Shi, Yan-Wei; Fan, Bu-Fang; Xue, Li; Wen, Jia-Ling; Zhao, Hu (Frontiers in Behavioral Neuroscience, 2017)
The amygdala, a critical structure for both Pavlovian fear conditioning and fear extinction, receives sparse but comprehensive dopamine (DA) innervation and contains dopamine D1 and D2 receptors. Fear extinction, which involves learning to suppress the expression of a previously learned fear, appears to require the dopaminergic system. The specific roles of D2 receptors in mediating associative learning underlying fear extinction require further study. Intra-basolateral amygdala (BLA) infusions of a D2 receptor agonist, quinpirole, and a D2 receptor antagonist, sulpiride, prior to fear extinction and extinction retention were tested 24 hours after fear extinction training for long-term memory (LTM). LTM was facilitated by quinpirole and attenuated by sulpiride. In addition, Α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor glutamate receptor 1 (GluR1) subunit, GluR1 phospho-Ser845, and N-methyl-D-aspartic acid (NMDA) receptor NR2B subunit levels in the BLA were generally increased by quinpirole and down-regulated by sulpiride. The present study suggests that activation of D2 receptors facilitated fear extinction and that blockade of D2 receptors impaired fear extinction, accompanied by changes in GluR1, GluR1-Ser845 and NR2B levels.